Control interno según el modelo coso ante la recaudación de tasa por el servicio de agua para riego en el sistema de riego Catarama de la prefectura de Los Ríos. - Magallón Parrales, Anggel Dayana (2025)
In the Department of Irrigation and Drainage of the Prefecture of Los Ríos, all users are visited in order to verify if in the following year they will continue with irrigation for their crops, in order to be able to apply the rates according to the quantity they need. Many users arrive at the socialization and registration for the eligible registry for the irrigation system, but do not fully comply with the payment of the fees corresponding to the six months of irrigation, taking into consideration that they must pay from the month of July. until the month of December, but upon reaching this date they have not fully complied with the previously agreed payment. The objective is to design an internal control system to avoid values owed by users of the Irrigation Department of the Prefecture of Los Ríos, the interview has been used as a data collection technique in a qualitative and non-experimental investigation, reaching the conclusion that they will improve the operational efficiency of the irrigation system, but will also contribute to its long-term sustainability, benefiting all users and guaranteeing efficient and responsible use of water resources.